Basic electronic devices and circuits - Patil, Mahesh B. (PHI Learning Private Limited, 2013)
This book provides detailed fundamental treatment of the underlying physics and operational characteristics of most commonly used semi-conductor devices, covering diodes and bipolar transistors, opto-electronic devices, junction field-effect transistors, and MOS transistors. In addition, basic circuits utilising diodes, bipolar transistors, and field-effect transistors are described, and examples are presented which give a good idea of typical performance parameters and the associated waveforms. A brief history of semiconductor devices is included so that the student develops an appreciation of the major technological strides that have made todays IC technology possible. Important concepts are brought out in a simple and lucid manner rather than simply stating them as facts. Numerical examples are included to illustrate the concepts and also to make the student aware of the typical magnitudes of physical quantities encountered in practical electronic circuits. Wherever possible, simulation results are included in order to present a realistic picture of device operation. Fundamental concepts like biasing, small-signal models, amplifier operation, and logic circuits are explained. Review questions and problems are included at the end of each chapter to help students test their understanding. The book is designed for a first course on semiconductor devices and basic electronic circuits for the undergraduate students of electrical and electronics engineering as well as for the students of related branches such as electronics and communication, electronics and instrumentation, computer science and engineering, and information technology.